Penerapan Strategi Pembelajaran Circuit Learning: Suatu Upaya dalam Meningkatkan Hasil Belajar Siswa - Syahrial Syahrial (Universitas Batanghari Jambi, 2019)
This research is motivated by the low student mathematics learning outcomes. The influencing factors are inactive students and lack of communication between students and students. This study aims to determine the effect of the application of the circuit learning strategy to students' learning outcomes in the cognitive and effective domains. This type of research is pre-experimental and the research design used is randomized control group only design. Based on the final test of learning outcomes obtained an average of mathematics learning outcomes in the experimental class 79.3 and the average mathematics learning outcomes of the control class 70. The results of the t-test analysis obtained tcount = 3.89 and ttable = 1.667 at the real level of 0.05. It is concluded that tcount> ttable accepts an alternative hypothesis (H1) that is the mathematics learning outcomes of the experimental class students is better than the control class. Analysis of the data in the affective domain obtained zcount = 3.83 and ztable = 1.64 at the real level of 0.05 thus zcount> ztable, in other words Hi is accepted meaning that student learning activities in the experimental class are better than the control class. Based on data analysis in the cognitive and affective domains it can be concluded that there is an influence of the application of the circuit learning strategy to student mathematics learning outcomes.